Cultura escrita digital: negociações para a produção de textos multimodais realizadas por crianças em processo de alfabetização e letramento digital - Íris Freua Assumpção (2022)
The investigation aimed to analyze the behaviors, gestures, attitudes and negotiation strategies used by children in the process of producing multimodal texts using computers, having as reference the concepts of “digital written culture” (CASSANY, 2002), “digital literacy” (MARSH, 2016; FRADE; COSCARELLI and RIBEIRO, 2014) and “multimodality” (KRESS and BEZEMER, 2009; JEWITT, 2005). From the perspective of this research, it is understood that literacy processes are also changed by the use of digital devices. Considering these new production contexts, using as a premise their possible influences on reading and writing practices of children in the literacy phase and the way in which texts are configured by different semiotic resources, the research sought to dialogue with these questions by proposing the following questions: what are the children's negotiation strategies during the production of multimodal texts in pairs? To answer these questions, a qualitative methodology was used and, from digitized books available for free on the internet, the children were motivated, in the research meetings, to produce different textual genres related to the theme and the dissemination of books in digital environments. The meetings took place remotely with eleven children from the 2nd year of Elementary School from a private school in Belo Horizonte. The production of texts involved multimodal resources, using collaborative writing strategies, using the Canva platform and the Google Presentations digital tool. Data analysis was based on the analysis of the content of interactions, interviews and productions, focusing on negotiations during the production processes of the participating children. The main results indicate that children are inserted in a digital written culture, being stimulated with visual and oral contents that reverberate in their texts. In writing, their practices are influenced by this culture, the suggestions of work partners and, in particular, the digital tools and platforms they use for this purpose, shaping their productions. Regarding the children's negotiations during the production of multimodal texts, it was found that they were related to the definition of roles, digital literacy, textual genre and the use of semiotic resources. The data show that the production of texts in digital environments expands capacities of expression and communication, creating more possibilities for children with the most diverse experiences with digital writing culture.